Estratégia baseada em recursos para o alcance da lucratividade e sustentabilidade : um estudo de caso - Spalenza, André Sarmento (2016)
This research aims to analyze how the strategy anchored in the Resource Based View (RBV) articulates the internal and external factors for the achievement of profitability and sustainability. From the perspective of RBV, it is understood that internal res